PROSES MANUFAKTUR TURBIN ANGIN SUMBU VERTIKAL TIPER CROSSFLOW - Mursal Setyawan (2020)
Crossflow turbines are turbines that work by means of air pressure being converted into kinetic energy. The air flow that causes the rotor to spin after first colliding with the turbine blade, then crossing (pushing) drives the second level blade. Crossflow turbines or also called Banki turbines are hydraulic turbines that can be classified as impulse turbines. Crossflow turbines have the advantage of a simple structure. Besides being used as a water turbine, crossflow turbines can also be used for vertical axis wind turbines. The assembly is done by rivet because welding cannot be done on aluminum. In addition to simplifying the work process, this rivet also reduces the cost and manufacturing time budget. Budget costs needed in making vertical axis wind turbines crossflow type are Rp. 1,700,000 and the time required for making vertical axis wind turbines crossflow type is 14 hours. Keywords: Wind turbine, crossflow, assembly